Pembelajaran kooperatif tipe group investigation untuk meningkatkan kemampuan pemahaman matematis mahasiswa calon guru sekolah dasar(Studi pada mahasiswa pendidikan guru sekolah dasar Universitas Majalengka tahun ajaran 2015/2016) - Iik Nurhikmayati (JP3M (Jurnal Penelitian Pendidikan dan Pengajaran Matematika), 2016)
This study aims to assess the problems of improving the ability of mathematical understanding and interaction between factors of learning and factors of early mathematical ability (subgroups of high, medium and low) to increase the ability of mathematical understanding through cooperative learning type group investigation. This study is a quasi-experimental research. The population is all students of the fifth-semester faculty PGSD primary and secondary education, Majalengka University 2015/2016. This study is a quasi-experimental research with the aim of reviewing the problems increase student’s mathematical reasoning abilities through learning with metaphorical thinking approach. In addition, this study also reviewing attitudes or responses of students to math and learning with metaphorical thinking approach. The populations of this study are all of the elementary school of class VIII students SMP Negeri 3 Lembang West Java province with a sample of 37  students of class VIIIA as the experimental group and 36 students of class VIIIB as the control group. The sampling was based on a purposive sampling technique. The research instrument consisted of pretest and posttest and attitude scale. The quantitative analysis using independent sample t-test and mann-witney test, while the qualitative analysis using was done descriptively. The results showed that increase in mathematical reasoning abilities students who received a learning with metaphorical thinking approach better than students who received a conventional learning. Analysis of the attitude scale questionnaire data showed that students have positive attitudes toward math and learning with metaphorical thinking approach.